Economic convergence in the EU and Eurozone. Issue 7 (11th November 2019) - Marelli, Enrico Piero; Parisi, Maria Laura; Signorelli, Marcello
Abstract : Purpose: The purpose of this paper is to analyse whether several groups of European countries are on track for real "conditional" economic convergence in per capita income and the likely speed of convergence. The paper focusses also on the changes of the convergence processes over time. Design/methodology/approach: Unlike the simple "absolute convergence", it explores the concept of "conditional" or "club" convergence. Moreover, it adopts the approach of extending the univariate model to take into account the panel dimension over an extended time interval and endogeneity. Findings: A process of real economic convergence has characterised the period under investigation (1995–2016), but, in general, the size and significance of the parameter is greater for the wide European Union (EU) area (EU25 and above) rather than the Eurozone (EZ). However, the crises occurred after 2008 caused most of such lower convergence in the Euro area. Research limitations/implications: This paper gives an estimate of the speed/time needed to several groups of European countries (EZ, in particular) to achieve real economic convergence. Future research could further develop the "stochastic" convergence concept. Originality/value: This is an analysis of convergence in enlarging EU and EZ for an extended period (including the big crisis period and the subsequent recovery). It shows that EZ experienced a drop in the speed of real convergence after 2008 and converge at lower speed than the EU. As a consequence, a specific budget for EZ would be important to provide adjustment mechanisms after potentially large shocks.